Representation of Egalitarian Concepts in the Tradition of the Banyumas Community in Ahmad Tohari’s Novels in the Perspective of Prophetic Philosophy - Teguh Trianton (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
Banyumas is an important area in Central Java that has a unique and distinctive culture, especially in terms of human relations. The uniqueness of Banyumas culture is recorded in literary texts and novels by Ahmad Tohari. The focus of this study is to reveal the egalitarian concept in human relations with fellow humans in the cultural treasures of Banyumas which is presented in the novels by Ahmad Tohari from the perspective of prophetic philosophy. This study was conducted to extract and conserve the values of local cultural wisdom. The method used is descriptive qualitative content analysis. The theory is literary anthropology and prophetic philosophy. As a result, in the case of human-human relations, Banyumas culture bequeathed the egalitarian concept as noble values that became the philosophy in social life. Egalitarian values are noble character values that need to be preserved. According to Banyumas culture, the egalitarian concept in horizontal relations is based on awareness and insight into the equality of human degrees before Allah SWT. Interaction between individuals takes place egalitarian by prioritizing transcendental humanism as the embodiment of prophetic philosophy simultaneously.